The Experience of Merit Wrapsody® Covered Stent for the Treatment of Popliteal Artery Aneurysms: an Alternative Device off the Shelf in a Case Series Report - Cristiano Dias de Matos Luz; Alexandre Mariante Horn; Vinícius Renan Dias; Vinícius Fornari; Rafael de Athayde Soares (Journal of Cardiology and Cardiovascular Medicine, 2025)
In this paper, we aimed to report the use of Merit Wrapsody® for popliteal artery aneurysms. We describe a case series involving 5 patients submitted to endovascular repair with Merit Wrapsody® for popliteal artery aneurysms. Merit Wrapsody® is a flexible self-expanding endoprosthesis indicated for use in hemodialysis patients for the treatment of stenosis or occlusion within the dialysis outflow circuit of an Arteriovenous (AV) fistula or AV graft, consisting of Nitinol, ePTFE, PTFE structure. In a case series communication, we aimed to describe the feasibility of a PTFE-lined stent for percutaneous treatment of conditions other than AV fistula obstruction. We report the successful use of Wrapsody® to percutaneously treat popliteal artery aneurysms. This case series illustrates the feasibility of the “off-label” use of self-expanded Wrapsody endoprosthesis to percutaneously treat arterial pathology conditions, especially popliteal artery aneurysms with satisfactory and excellent results.